Corrosion condition evaluations of historic concrete icons. (June 2015) - Crevello, Gina; Hudson, Nancy; Noyce, Paul
Abstract: Corrosion condition assessments of historic concrete structures can provide the owner with invaluable information regarding the current condition of the structure, the factors contributing to the corrosion damage, and can also project when the structure may exhibit further material loss. This information is vital to be proactive in the repair process which is imperative to minimize loss to the structure. When dealing with a highly significant concrete structure, the investigative team is often faced with restrictive parameters limiting the amount of data which can be collected. This paper discusses challenges in preserving 'historic concrete' and provides four case studies of predictive corrosion condition assessments which were carried out to help in the decision making process.